Arts As A Possibility Of Health Promotion: A Proposal For Primary Care - Teixeira-Machado, Lavinia; Coutinho, Eduardo Tessari (Advances in Social Sciences Research Journal, 2018)
This manuscript discuss the arts as a possible and effective intervention in primary health care. The aim is to highlight health care and promotion policies in Brazil and how education and lifestyle modification can be accomplished. Arts in health promotion and well-being enable and influence the overcoming of the precariousness and inequity of health actions. Primary Health Care is the most efficient way of organizing health system. In the sphere of health promotion policy, community participation stands out as essential to ensure its effectiveness. Health education through arts generates an interface with culture, being fundamental for the promotion of conditions that improve daily activities. Edification of health education ways, using arts, fosters a new vehicle for expression, interpretation, representation and life style. Arts socialize information inherent in various artistic forms, by bringing popular knowledge closer to educational success. As value is conferred on lived experience, art meaning is essentially linked to health. Arts enhance verbal and non-verbal communication, flooded with meanings and symbolism, there are interferences in feelings, in the way people perceive themselves and perceive the world around them, and consequently how they shape their health and their being in the society in which they live.